Actual problems of education in the Eurasian region in the second half of the 20th and the beginning of the 21st century (On the example of Russia and Mongolia) - Artamonova Т.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
The trajectories of the development of the state education system in Russia and Mongolia in the twentieth century had similar trends. They reflected the common problems and achievements of building the foundations of public education. Currently, these countries are faced with the problem of denationalization and defundamentalization of the public education system. Special research attention is required by the fact of the devaluation of higher education with an increasing demand for it among young people. Russia and Mongolia are experiencing the influence of globalization and Westernization, which threatens to result in the loss of pan-Eurasian values in education today. Common Eurasian values include good neighborliness, a strong and friendly family, peace, mutual assistance, and respect for the natural principle. These values will make it possible to resist the globalist unification onslaught and the destruction of national identity. The common life priorities of the peoples of Eurasia have united them for centuries over national, cultural, and religious differences. The researchers note that even in the new geopolitical conditions, the complementarity of interethnic relations between Russian and Mongolian youth persists. These data were obtained during interdisciplinary research among students of the Altai Territory of Russia and the Khovda Aimag of Mongolia. The article provides recommendations for strengthening cooperation between the countries of the Eurasian region in the field of education.